SOCIAL MEDIA FEAR OF MISSING OUT (FOMO) TO GEN Z: THE ROLE OF GREEN MARKETING COMMUNICATION AND SOCIAL INFLUENCE TO PURCHASE INTENTION - Stella Laurenc Widjaya; Maria Dini Gilang Prathivi; Antonius Juniarto (LPSDI Bina Patria, 2024)
This research was conducted to determine whether social media marketing and social influence influence the purchase intention of Fore Coffee products in West Jakarta with FOMO (Fear of Missing Out) mediation. This research addressed all Fore Coffee consumers at Jakarta’s outlets as many as 305 Gen Z respondents. The research method carried out in this study is the quantitative method. Data collection through online surveys through Google Forms. Sampling is carried out by non-probability sampling using the accidental sampling method and using SmartPLS (Partial Least Square) software. The results of this study found that social media marketing and social influence influence the buying interest of Fore Coffee products mediated by FOMO